Communication—Edge Quality Contribution on the Electrical Impedance of Lithium-Ion Batteries Electrodes. Issue 8 (20th April 2020) - Carbonari, Gilberto; Müller, Verena; Scurtu, Rares-George; Memm, Michaela; Hoffmann, Alice; Wohlfahrt-Mehrens, Margret
Abstract : Lithium-ion batteries (LiBs) industrial production requires a large number of skills in many scientific fields. The process starts from the electrodes manufacturing and ends with the battery formation. Electrodes cutting is undoubtedly a crucial step as it could turn out to be one of the bottlenecks for a fast and efficient production. In this paper, we propose a quicker and cheaper method to evaluate the electrical contact resistance between coating and current collector (RContact ) by using impedance spectroscopy (EIS) to compare different cutting methods. The results show the existence of a cutting technique—cell performance relationship.